Synthesis of a new phenoxycyclophosphazene derivative Schiff base and its Ru(II), Co(III) complexes - Nergiz, Kubra; Demirhan, Nebahat (IOS PRESS, 2023)
In this study, a new phenoxy cyclophosphazene derivative bis(2-formyl-phenyl)4,4,6,6-bis[spiro(2',2-dioxy1',1biphenylyl)]cyclotriphosphazene (P2) was synthesis in by the reactions between 2,2-dichloro-4,4,6,6-bis[spiro(2',2dioxy-1',1biphenylyl)]cyclotriphosphazene (P1) with salicyl aldehyde in presence of K2CO3 at room temperature in THF under argon atmosphere, and the newphenoxy cyclophosphazene derivative Schiff bases which are containing long-chain alkyl groups and salicyl aldehyde, bis[spiro(2',2-dioxy-1',1biphenylyl)2,3-diphenoxy-2-imidododesyl]cyclotriphosphazene (P3) synthesized by condensation reactions in suitable conditions with (P2) and dodecylamine. Synthesized ligands have been investigated with the methods of FTIR, P-31 NMR, Uv-vis, MS spectroscopies, elemental and thermal analysis (TGA and DSC). Co(III), Ru(II) complexes were synthesized (L/M) 1:2 ratio and characterized FTIR, UV-vis and MS spectra, together with elemental and thermal analysis.
Keywords: Cyclotriphosphazene; Schiff bases; phenoxyphosphazane; transition metal complexes; BIOLOGICAL-ACTIVITIES; DNA INTERACTIONS; PHOSPHAZENES; LIGAND; Chemistry